52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0197
|View full text |Cite
|
Sign up to set email alerts
|

Roll-modes generated in turbulent boundary layers with passive surface modifications

Abstract: A unique class of directional surfaces arranged in a converging-diverging (herringbone) pattern are studied experimentally in a zero pressure gradient turbulent boundary layers. Hot-wire measurements using both single and cross-wire show that these small surfaces are able to generate large-scale counter rotating roll-modes/vortices within the turbulent boundary layer, resulting in dramatic spanwise variation in the boundary layer thickness δ (50% variation for the strongest case). The results reveal that above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Inspired by this finding, a series of experimental studies on convergent-divergent riblets has been carried out in a flat plate turbulent boundary layer at the University of Melbourne. Similar results to those reported by Koeltzsch et al 21 were also obtained by Nugroho et al 23 Using a cross-wire, Nugroho et al 24 revealed the presence of a large-scale counter-rotating roll mode in the time-averaged flow field in cross-stream planes. Their finding was also confirmed and extended by Kevin et al 25 with their stereoscopic PIV measurements.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Inspired by this finding, a series of experimental studies on convergent-divergent riblets has been carried out in a flat plate turbulent boundary layer at the University of Melbourne. Similar results to those reported by Koeltzsch et al 21 were also obtained by Nugroho et al 23 Using a cross-wire, Nugroho et al 24 revealed the presence of a large-scale counter-rotating roll mode in the time-averaged flow field in cross-stream planes. Their finding was also confirmed and extended by Kevin et al 25 with their stereoscopic PIV measurements.…”
supporting
confidence: 82%
“…This observation is in agreement with the finding from previous experiments. [23][24][25] A comparison of the control effects between convergent-divergent riblets and synthetic jet is provided. In the active flow control experiments with synthetic jets, the upwash and downwash of fluid in the near-wall region are induced by the rotations of hairpin legs, 36,37 with an upwash leading to a decreased local skin friction and a downwash resulting in an increased one.…”
Section: Large-scale Vortical Structures In the Cross-stream Planementioning
confidence: 99%
“…(They also showed that streamwise velocity fluctuations were elevated within the analogous LMP, which is consistent with the findings of Mejia-Alvarez & and Barros & Christensen (2014), though for a profoundly different topography.) In fact, another very recent study by Nugroho et al (2014) showed that the spanwise heterogeneities exhibited counter-rotating mean flow vortices with the same rotational sense as observed by Barros & Christensen (2014). Such patterns are consistent also with those reported by Reynolds et al (2007) for flow over regular arrays of cubes wherein mean flow heterogeneity occurred at integer multiples of the periodic spanwise roughness spacing and for which enhanced turbulence intensity was noted coincident with regions of reduced streamwise momentum (LMPs).…”
supporting
confidence: 82%
“…Recent experimental and numerical work (Mejia-Alvarez & Christensen 2010, 2013Nugroho et al 2013Nugroho et al , 2014Willingham et al 2013;Barros & Christensen 2014) has shown that spanwise heterogeneous, streamwise-elongated roughness has a dramatic influence on dynamics of the turbulent boundary layer. Specifically, the presence of a secondary mean flow in the form of counter-rotating roll cells has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation